RESEARCH SKILLS OF A FUTURE PHYSICS TEACHER AS A COMPONENT OF HIS PROFESSIONAL ACTIVITY IN A MIXED (OFFLINE AND ONLINE) ENVIRONMENT TRAINING - Битибаева, Жазира; Насирова, Диана; Рыстыгулова, Венера; Мырзатай, Майра (Pedagogy and Psychology, 2022)
Mastering the system of subject skills is carried out using a number of mental operations, such as comparison, classification, analysis, synthesis, etc. They form an important part of the educational process and should be in the field of view of teachers. Since the quality of the formation of mental operations depends on the success of mastering future specialists not only subject knowledge, but also research skills and abilities. The positive results of the formation of research skills in the context of online learning are also evidenced by studies aimed at studying the factors influencing the changes caused by the pandemic crisis. The success of education with the introduction of online technologies and innovations, as well as targeted training of future teachers should become the basis for the development of effective forms of work of the teaching staff and the policy of universities in general for high-quality online education in crisis situations.